Avaliação de diferentes fontes de fósforo na nutrição de ruminantes - Barreto, Julio Cezar (2006)
This study was carried out to evaluate the effects of different phosphorus sources on apparent partial and total nutrient digestibility, ruminal parameters, microbial efficiency synthesis and plasma phosphorus of growing cattle diets. Four Holstein steers with liveweight of 280 kg and implanted with ruminal and duodenal cannulas were used. The experimental design was a 4 x 4 Latin Square and the treatments were four supplemental phosphorus sources: dicalcium phosphate (DP), supertriple phosphate (SP), monoammonium phosphate (MP) and Araxa rock phosphate (ARP). Phosphorus sources did not affect intake, fecal flow, apparent ruminal and intestinal digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF) and non fiber carbohydrates (NFC). Phosphorus apparent absorption was lower (P<.05) for ARP, in contrast with DP and MP. Animals receiving ARP presented (P<.05) higher intake, fecal flow, duodenal flow, ruminal disappearance and total disappearance of fluoride (F). Animals receiving ARP were fed fluoride levels higher than acceptable to avoid toxicity. Phosphorus sources did not affect (P>.05) plasma phosphorus, nitrogen intake, microbial efficiency synthesis and ruminal bacteria composition. Treatments did not affect (P>.05) ruminal pH and ruminal ammonium concentration. These results suggest that it is possible to use supertriple phosphate and monoammonium phosphate as a replacement for dicalcium phosphate. Concerning to ARP, there was no effect (P>.05) on fermentation and digestion parameters, but animal phosphorus requirements should be taken into account because apparent phosphorus absorption was lower for this source, and fluoride levels were higher than recommended by research.